Investigation of agility levels according to different sport branches - BILAL Demırhan; Beksultan Botobaev; Kanat Canuzakov; Serdar Geri (Selcuk University, 2017)
The aim of this study is to examine the agility levels according to sports branches. A total of 50 male athletes, consisting of 10 wrestlers, 10 volleyball players, 10 boxers, 10 basketball players and 10 football players, whose average ages were 20.94 ± 1.64, participated in the study voluntarily. Illinois Agility Test has been applied on the athletes. The agility levels of the participating athletes have been recorded in seconds. The level of agility have been determined in the Football players as 14.72 sec, in Wrestlers as 14.82 sec, in Basketball players as 16.15 sec, in Boxers as 14.64 sec and in Volleyball players as 15.93 sec. As a result, the agility level of boxers has been determined higher than other branches and the lowest level of agility has been observed in basketball players. It is thought that the differences in agility values ​​are related to the sports branches.